Dynamic Approaches to Global Economic Challenges Festschrift in Honor of Karl Farmer - Bednar-Friedl, Birgit; Kleinert, Jörn (Springer International Publishing : Imprint: Springer, 2016)
This book addresses three big economic challenges from a dynamic perspective: European integration, economic growth, and global climate change. In the light of the recent crises of the European Union (EU), the first part of the book deals with challenges to the real, monetary and fiscal integration of the EU and required institutional adjustments. The second part of the book addresses fundamental challenges of advanced market economies like economic growth and changes of technologies. The final part focuses on the global challenge of climate change from an economic perspective and discusses policy strategies for a successful mitigation of climate change.